5-HT1F receptor agonism induces mitochondrial biogenesis and increases cellular function in brain microvascular endothelial cells - Scholpa, Natalie E.; Simmons, Epiphani C.; Thompson, Austin D.; Carroll, Seth S.; Schnellmann, Rick G. (Frontiers in Cellular Neuroscience, 2024)
Vascular and mitochondrial dysfunction are well-established consequences of multiple central nervous system (CNS) disorders, including neurodegenerative diseases and traumatic injuries. We previously reported that 5-hydroxytryptamine receptor 1F receptor (5-HT1FR) agonism induces mitochondrial biogenesis (MB) in multiple organ systems, including the CNS. Lasmiditan is a selective 5-HT1FR agonist that is FDA-approved for the treatment of migraines. We have recently shown that lasmiditan treatment induces MB, promotes vascular recovery and improves locomotor function in a mouse model of spinal cord injury (SCI). To investigate the mechanism of this effect, primary cerebral microvascular endothelial cells from C57bl/6 mice (mBMEC) were used. Lasmiditan treatment increased the maximal oxygen consumption rate, mitochondrial proteins and mitochondrial density in mBMEC, indicative of MB induction. Lasmiditan also enhanced endothelial cell migration and tube formation, key components of angiogenesis. Trans-endothelial electrical resistance (TEER) and tight junction protein expression, including claudin-5, were also increased with lasmiditan, suggesting improved barrier function. Finally, lasmiditan treatment decreased phosphorylated VE-Cadherin and induced activation of the Akt-FoxO1 pathway, which decreases FoxO1-mediated inhibition of claudin-5 transcription. These data demonstrate that lasmiditan induces MB and enhances endothelial cell function, likely through via the VE-Cadherin-Akt-FoxO1-claudin-5 signaling axis. Given the importance of mitochondrial and vascular dysfunction in neuropathologies, 5-HT1FR agonism may have broad therapeutic potential to address multiple facets of disease progression by promoting MB and vascular recovery.